1998
DOI: 10.1002/(sici)1099-0690(199812)1998:12<2769::aid-ejoc2769>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

A General Synthesis of Disubstituted Rubicenes

Abstract: The synthesis of novel disubstituted rubicenes 1a–k is described. Starting from 1,5‐dichloroanthraquinone and aryllithium reagents 3, the diol adducts 4 are reduced and the resulting diarylanthracenes 5 are cyclized to afford the title compounds in fair to good overall yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The synthesis was performed using previously established platinum‐mediated macrocyclization methods . Rubicene with two boryl groups ( 2 ) at the 5‐ and 12‐positions was prepared from dichlororubicene ( 1 ) by Miyaura borylation and subjected to the Pt‐mediated macrocyclization (Scheme ) . Without isolation of the macrocyclic Pt complexes, subsequent reductive elimination was performed after ligand exchange with PPh 3 to afford [ n ]CR.…”
Section: Figurementioning
confidence: 99%
“…The synthesis was performed using previously established platinum‐mediated macrocyclization methods . Rubicene with two boryl groups ( 2 ) at the 5‐ and 12‐positions was prepared from dichlororubicene ( 1 ) by Miyaura borylation and subjected to the Pt‐mediated macrocyclization (Scheme ) . Without isolation of the macrocyclic Pt complexes, subsequent reductive elimination was performed after ligand exchange with PPh 3 to afford [ n ]CR.…”
Section: Figurementioning
confidence: 99%
“…In previous work we have reported the preparation and alkylation of 5,12-dihydroxyrubicene [1][2]. Although alkylation of the latter compound with benzyl bromides proceeded quite smoothly, reaction of this rubicene derivative with simple aliphatic bromides and tosylates turned out to fail.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have used the highly fluorescing and photostable rubicene as a core in dendrimer chemistry [1]. A new approach towards disubstituted rubicenes was devised [2].…”
Section: Introductionmentioning
confidence: 99%
“…Being inspired by an interesting heptacyclic arene of rubicene [6], we decided to start a new program focused on the synthesis of annulated analogues of azafluoranthene and heteroazulene, starting from the dervatives of PQ [7]. During our preliminary studies we observed the possibility from the same starter, i.e.…”
Section: Dpipq Cpdppq Ptnamentioning
confidence: 93%